Montmorillonite for selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Mate, Vivek R.; Rode, C. V. (Applied Clay Science, 2009)
Performances of montmorillonite titanium silicate (TS-1) and dodecatungstophosphoric acid (DTP) were compared for the hydroxyalkylation of p-cresol into dihydroxydiarylmethane (DAM). Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of montmorillonite was mainly responsible rather than only the stronger acidity of bulk DTP for its highest catalytic activity for selective hydroxyalkylation of p-cresol to DAM. The selectivity to DAM could be enhanced by adjusting reaction conditions like mole ratio of p-cresol to formaldehyde, reaction temperature, catalyst concentration, solvent and reaction time. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Dihydroxydiarylmethane; Hydroxyalkylation; Montmorillonite; Solid acids

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

MCM-41 supported phosphotungstic acid for the hydroxyalkylation of phenol to phenolphthalein - Jha, Ajay; Garade, Ajit C.; Mirajkar, Subhash P.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
A novel application of phosphotungstic acid, H3PW12O40 (PWA) supported on MCM-41 molecular sieve as a solid acid catalyst has been demonstrated for the synthesis of phenolphthalein by hydroxyalkylation of phenol and phthalic anhydride. PWA/MCM-41 (20%) showed the highest activity as compared to that of parent PWA and MCM-41 individually, due to the excellent dispersion of PWA on MCM-41 leading to the redistribution of Bronsted and Lewis acid sites on MCM-41. The effect of PWA loading on phthalic anhydride conversion and phenolphthalein selectivity was also studied. All these prepared catalysts were characterized by XRD, N-2 adsorption-desorption isotherm, pyridine-FTIR, and NH3-TPD. The effect of various reaction parameters, namely, mole ratios, catalyst concentration, temperature, reaction time, and percentage of PWA present in the catalysts on conversion and selectivity of products has been also investigated. The utility of 20% PWA/MCM-41 catalyst was established by its efficient activity for hydroxyalkylation of phenol and p-cresol with formaldehyde to the corresponding dihydroxydiarylmethane products.

Magnetically separable single-site Ti-Fe3O4@MCM-41 catalyst for selective epoxidation of olefins - Jha, Ajay; Patil, Chetana R.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2013)
Magnetically separable Ti-Fe3O4@MCM-41 (Ti-MS) catalysts were prepared by postgrafting Ti with varying loading on mesoporous silica containing dispersed magnetite. The hexagonal structure of Ti-MS catalysts with a periodicity in the pores and a highly ordered hexagonal matrix was established by X-ray diffraction and transmission electron microscopy, while diffuse reflectance UV showed the isolated tetrahedral Ti species coordinated with O2-. From the Fourier transform infrared studies, the extent of Ti-O-Si linkage was found to increase with increase in Ti-loading from 1 to 5 wt %beyond which (10%), the intensity of Ti-O-Si band decreased due to the polymerization of the Ti on the silica surface. Silanol groups on the surface of silica interact with the precursor Ti((OPr)-Pr-i)(4) to give site isolated tetrahedral Ti-species responsible for complete selectivity to the epoxide in the epoxidation of cyclooctene. The magnetic property facilitated easy recovery of the catalyst for its successful eight recycles showing its stability under reaction conditions.

Metal cation-exchanged montmorillonite clay as catalysts for hydroxyalkylation reaction - Jha, Ajay; Garade, Ajit C.; Shirai, M.; Rode, C. V. (Applied Clay Science, 2013)
Several solid acid catalysts were prepared by exchanging metal cations such as Zn2+, Fe3+ and Al3+ with montmorillonite clay. Among these, Al-montmorillonite showed the highest acidity determined by the pyridine-IR as well as NH3-TPD methods. A systematic comparison of the performance of these catalysts along with parent montmorillonite was carried out for the hydroxyalkylation of p-cresol with formaldehyde to give 2, 2'-methylenebis (4-methyl phenol) (DAM). It was found that the activity of these catalysts was in accordance with the increase in acidity of parent montmorillonite after the exchange of cations in the order of Zn2+, Fe3+ and Al3+. The selectivity pattern was also influenced by the exchanged cations. Since Al-montmorillonite showed the highest conversion of 51% with 98% selectivity to DAM, the effects of various reaction parameters, namely, mole ratio, catalyst concentration, temperature, reaction time on conversion and selectivity pattern were also studied using the same catalyst This catalyst also showed an excellent stability as evidenced by its eight times reuse. (C) 2012 Published by Elsevier B.V.
Keywords: Cations-exchanged clay; Montmorillonite; NH3-TPD; Pyridine-IR